Nuevo Baztán: a commitment to educating in free time - Villajos González, Luis (Pulso. Revista de educación, 2006)
This article is about the experience of Leisure Education and Community Development in a town in the South eastern province of Madrid. It is an analysis of the uniqueness of Nuevo Baztán (Madrid, Spain)), a country town with programs for Educational Free-time Activities typical of urban settings. The program began in the early 1980´s and has continued into the 21st Century, currently focusing on Socio-cultural Encouragement geared towards teenagers and youngsters alike as part of a service sponsored by the town hall.